Does a multimedia education program work as a remedy for stress and burden in family caregivers of elderly heart attack patients? A clinical trial study - Maliheh Abbasi; Nadia Kolbadinezhad; Somayeh Rostami; Mahya Ahmadi (BMC Nursing)
Abstract Background Supportive care has been found to improve quality of life and reduce the disease burden for aging individuals. After a heart attack, elderly patients often require a caregiver. In developing communities, caregiving responsibilities frequently fall on family members. Accordingly, we designed a randomized controlled clinical trial to assess the effect of an educational program on perceived stress and care burden among family caregivers of elderly heart attack patients. Method In this clinical trial (IRCT20220905055894N1, 01/02/2023), family member caregivers were the study participants, assigned to either intervention or control groups using a simple random sampling method. The control group received only routine in-home caregiving information, without additional nurse training or support, whereas the intervention group received multimedia-based training, monitoring, and communication support from a trained nurse over one month. Perceived stress levels and caregiving burden were measured using the Perceived Stress Scale (PSS) and the Caregiving Burden Inventory, respectively. Results Before the intervention, a high level of caregiving stress (34.07 ± 8.61 in the control group vs. 34.17 ± 8.62 in the intervention group) and burden (77.7 ± 15.51 in the control group vs. 79 ± 15.6 in the intervention group) was observed. After one month of intervention, the average scores of stress and burden remained unchanged in the control group, whereas the intervention group showed a significant reduction (P < 0.001). The inter-group comparison revealed lower levels of stress and care burden in the intervention group (P < 0.001). Conclusion A brief multimedia education intervention could help alleviate the stressful conditions experienced by family caregivers of elderly heart attack patients. Future studies could investigate whether a more extended educational program would have more lasting effects.